Epidemiological and genetic data supporting the transmission of ancylostoma ceylanicum among human and domestic animals - Ngui, R.; Lim, Y. A. L.; Traub, R.; Mahmud, R.; Mistam, M. S. (Public Library of Science, 2012)
Background: Currently, information on species-specific hookworm infection is unavailable in Malaysia and is restricted worldwide due to limited application of molecular diagnostic tools. Given the importance of accurate identification of hookworms, this study was conducted as part of an ongoing molecular epidemiological investigation aimed at providing the first documented data on species-specific hookworm infection, associated risk factors and the role of domestic animals as reservoirs for hookworm infections in endemic communities of Malaysia. Methods/Findings: A total of 634 human and 105 domestic canine and feline fecal samples were randomly collected. The overall prevalence of hookworm in humans and animals determined via microscopy was 9.1 (95 CI = 7.0-11.7) and 61.9 (95 CI = 51.2-71.2), respectively. Multivariate analysis indicated that participants without the provision of proper latrine systems (OR = 3.5; 95 CI = 1.53-8.00; p = 0.003), walking barefooted (OR = 5.6; 95 CI = 2.91-10.73; p < 0.001) and in close contact with pets or livestock (OR = 2.9; 95 CI = 1.19-7.15; p = 0.009) were more likely to be infected with hookworms. Molecular analysis revealed that while most hookworm-positive individuals were infected with Necator americanus, Ancylostoma ceylanicum constituted 12.8 of single infections and 10.6 mixed infections with N. americanus. As for cats and dogs, 52.0 were positive for A. ceylanicum, 46.0 for Ancylostoma caninum and 2.0 for Ancylostoma braziliense and all were single infections. This present study provided evidence based on the combination of epidemiological, conventional diagnostic and molecular tools that A. ceylanicum infection is common and that its transmission dynamic in endemic areas in Malaysia is heightened by the close contact of human and domestic animal (i.e., dogs and cats) populations.